Resolving the Strategy Paradox Applying the Strategic Flexibility: A Case Study of PT BNI Life Insurance - Widati , Endah (Universitas Prasetiya Mulya, 2012)
Over decades, the business environment has changed dramatically as it has been affected by the changing of environmental needs and demand. The difference level of environmental turbulence characteristics will create new business competitive landscape for all companies in any industries. Environmental turbulence is also marked by dynamics, complexity and unpredictability business environment. In such a situation, a company will be difficult to adapt the environmental changes. In a turbulent environment, a company is demanded to be able to adapt. Many researchers argue that in a turbulent environment, a company is not only demanded for having adaptive ability but also flexible ability either structural, operational or strategic. The fast pace of environmental changes provide managers unpredictable outcomes of their strategic alternative or strategic commitment. This collision of strategic commitment and strategic uncertainty is causing what Raynor (2007) named as the strategy paradox. Every company can be a victim of the strategy paradox if they cannot align their strategy with the environmental changes. Raynor (2007) pointed out that one of the ways to resolve strategy paradox is implementing strategic flexibility in term of ex ante action (proactive actions). One of the industries in Indonesia that also experiences the turbulent environment is insurance industry. This study examines and investigates the strategic flexibility as a way to resolve strategy paradox at PT BNI Life Insurance.